ABSOLUTE CONFIGURATION OF 18-ACETOXY-CIS-CLERODA-3,13E-DIEN-15-OIC ACID - Iván Brito; Jorge Bórquez; Diego Robledo; Mario J. Simirgiotis; Alejandro Cárdenas (Journal of the Chilean Chemical Society, 2018)
In this paper we report the absolute configuration which has been determined from the refinement of the Flack parameter, x = 0.05(5), which indicate that the correct configuration had been assigned against 1353 (99%) CuKα Bijvoet pairs. On this basis the absolute configuration was assigned as C5R, C8S, C9R and C10S. The structure of 18-acetoxy-cis-cleroda-3,13E-dien-15-oic acid consists of a clerodane skeleton and the corresponding methyl groups are α-oriented (C8, C9) while C5 is β-oriented. The acidic lateral chain is β-oriented and the double bond between C13 and C14 has E isomeric. The ciclohexene, cyclohexane rings are cis fused, and in an sofa and chair conformation respectively. In the crystal the molecules are linked by one intermolecular OH⋅⋅⋅O hydrogen bond forming 1D-dimensional chain with distance donor-acceptor of 2.060(6)Å with graph-set notation C1 1 (15).